A colony multiplex quantitative PCR-Based 3S3DBC method and variations of it for screening DNA libraries. - Yang An; Atsushi Toyoda; Chen Zhao; Asao Fujiyama; Kiyokazu Agata (PLoS ONE, 2015)
A DNA library is a collection of DNA fragments cloned into vectors and stored individually in host cells, and is a valuable resource for molecular cloning, gene physical mapping, and genome sequencing projects. To take the best advantage of a DNA library, a good screening method is needed. After describing pooling strategies and issues that should be considered in DNA library screening, here we report an efficient colony multiplex quantitative PCR-based 3-step, 3-dimension, and binary-code (3S3DBC) method we used to screen genes from a planarian genomic DNA fosmid library. This method requires only 3 rounds of PCR reactions and only around 6 hours to distinguish one or more desired clones from a large DNA library. According to the particular situations in different research labs, this method can be further modified and simplified to suit their requirements.